2022
DOI: 10.3168/jds.2021-21553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary butyrate supplementation and oral nonsteroidal anti-inflammatory drug administration on serum inflammatory markers and productivity of dairy cows during the calving transition

Abstract: Dairy cattle experience inflammation during the calving transition period, and butyrate and nonsteroidal anti-inflammatory drugs (NSAID) are expected to reduce the inflammation. Our objective was to evaluate the effects of dietary butyrate supplementation and oral NSAID administration on feed intake, serum inflammatory markers, plasma metabolites, and milk production of dairy cows during the calving transition period. Eighty-three Holstein cows were used in the experiment with a 2 × 2 factorial arrangement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 78 publications
1
6
1
Order By: Relevance
“…In the present study, cows with MgB supplementation produced more milk during the first week of lactation compared to the Control animals. This finding is in contrast to that of other studies, with either sodium butyrate [ 6 ] and calcium butyrate [ 8 ], which failed to find a significant benefit on lactation performance when supplemented to dairy cows prepartum. It is not clear to what extent the lower number of experimental animals (<20 per group) and/or type of diet in these studies may have contributed to these contrasting findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, cows with MgB supplementation produced more milk during the first week of lactation compared to the Control animals. This finding is in contrast to that of other studies, with either sodium butyrate [ 6 ] and calcium butyrate [ 8 ], which failed to find a significant benefit on lactation performance when supplemented to dairy cows prepartum. It is not clear to what extent the lower number of experimental animals (<20 per group) and/or type of diet in these studies may have contributed to these contrasting findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Kowalski et al [ 6 ] found no benefit of butyrate on lactation performance when sodium butyrate was given to dairy cows prepartum. Recently, a study with calcium butyrate confirmed these findings [ 8 ].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…All procedures were approved by the University of Alberta Animal Care and Use Committee for Livestock (AUP00003364). This experiment was conducted in tandem with Engelking et al (2022).…”
Section: Short Communication Physiologymentioning
confidence: 99%
“…L. E. Engelking, 1 M. Gobikrushanth, 2 M. Oba, 1 and D. J. Ambrose 1 * and dietary butyrate concentration determination, are included in Engelking et al (2022). Experimental diets were fed ad libitum through individual mangers at 0800 h, from 28 ± 3 d before expected calving date to 24 ± 3 d after calving.…”
Section: Effects Of Dietary Butyrate Supplementation and Oral Nonster...mentioning
confidence: 99%